Social Media Marketing And Customer Satisfaction - Almansyah Rundu Wonua; Rina Sovianti; Andriya Risdwiyanto; I Nyoman Tri Sutaguna; Arief Yanto Rukmana (Lembaga Pengembangan Kinerja Dosen, 2023)
Researcher This employs a scientific method. A case study at the Upnormal shop in Jatinangor, Sumedang Regency, served as the design for this project. This study intends to ascertain the impact of online delivery services and social media marketing on consumer satisfaction. The study was carried out between April and July 2023. The Upnormal Shop in Jatinangor, Sumedang Regency, which houses a number of MSMEs, particularly in the food sector, was chosen as the study's venue. Consumers who buy food in Jatinangor, Sumedang Regency, make up the study's population.